VD_FINDINFO HC / 2017 / 1124 vom 13. Dezember 2017 - VD Tribunal cantonal (2017)
DÉCISION INCIDENTE, CONDITION DE RECEVABILITÉ, CONNEXITÉ MATÉRIELLE | 202 CPC (CH), 227 al. 1 CPC (CH), 237 CPC (CH), 308 al. 1 let. a CPC (CH)